CP6 Anopthalmia and dysembryoplastic neuroepithelial tumours in a family with Noonan syndrome and a novel PTPN11 mutation. Issue 11 (22nd October 2010) - Mir, R; Chong, K; Benett, C; Aldin, A; Balen, F; Kraus, A; Taylor, R
Abstract : We describe previously unreported features of anophthalmia/micropthalmia and multifocal dysembryoplastic neuroepithelial tumours (DNET) in a family with Noonan syndrome. Noonan syndrome (NS) is an autosomal dominant developmental disorder which is caused by aberrant up-regulated signalling through Ras GTPase. The proband has Noonan syndrome and presented with complex partial seizures. MRI brain showed appearance of DNET. Affected family members have the same novel heterozygous PTNP11 mutation (1471 C>T), replacing a serine for proline at codon 491 in exon 13. We suggest that altered recruitment of the PTPN11 gene product to fibroblast growth factor receptor 2 (FRS2α) gives rise to anopthalmia (as seen in proband's maternal relatives) and abnormal cortical development. There is no previous report of anopthalmia or microphthalmia as part of the NS phenotype or in conjuction with PTNP11 mutation. There is also no previous report of DNET in association with NS or PTNP11 mutations. DNET has once been described in association with a cloboma and there is one previous report of cortical dysplasia in NS.